Focused breastfeeding counselling improves short‐ and long‐term success in an early‐discharge setting: A cluster‐randomized study. Issue 4 (14th February 2017) - Nilsson, Ingrid M. S.; Strandberg‐Larsen, Katrine; Knight, Christopher H.; Hansen, Anne Vinkel; Kronborg, Hanne
Abstract: Length of postnatal hospitalization has decreased and has been shown to be associated with infant nutritional problems and increase in readmissions. We aimed to evaluate if guidelines for breastfeeding counselling in an early discharge hospital setting had an effect on maternal breastfeeding self‐efficacy, infant readmission and breastfeeding duration. A cluster randomized trial was conducted and assigned nine maternity settings in Denmark to intervention or usual care. Women were eligible if they expected a single infant, intended to breastfeed, were able to read Danish, and expected to be discharged within 50 hr postnatally. Between April 2013 and August 2014, 2, 065 mothers were recruited at intervention and 1, 476 at reference settings. Results show that the intervention did not affect maternal breastfeeding self‐efficacy (primary outcome). However, less infants were readmitted 1 week postnatally in the intervention compared to the reference group (adjusted OR 0.55, 95% CI 0.37, −0.81), and 6 months following birth, more infants were exclusively breastfed in the intervention group (adjusted OR 1.36, 95% CI 1.02, −1.81). Moreover, mothers in the intervention compared to the reference group were breastfeeding more frequently ( p < .001), and spend more hours skin to skin with their infants ( p < .001). The infants were less often treated for jaundice ( p = 0.003) and there was more paternal involvement ( p = .037). In an early discharge hospital setting, a focused breastfeeding programme concentrating on increased skin to skin contact, frequent breastfeeding, good positioning of the mother infant dyad, and enhanced involvement of the father improved short‐term and long‐term breastfeeding success.